Prototype Continuous Glucose Monitor - Sternberg, James C. (1968)
The document describes the components, operating instructions, troubleshooting, and maintenance of a prototype device. Handwritten notes were added to pages 27 and 31. The Glucose Analyzer was developed by James Sternberg in 1969 and was one of several very successful medical testing and analysis instruments that Beckman Instruments produced in the 1970s. Its size, speed, and price enabled doctors to get fast, in-house results, instead of sending patients’ blood samples to a lab and awaiting a report.
Keywords: Medical laboratories--Equipment and supplies; Glucose--Analysis; Blood sugar--Analysis; Scientific apparatus and instruments; Beckman Instruments, Inc.